2009
DOI: 10.1200/jco.2008.18.9563
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Postoperative Adjuvant Radiotherapy After Radical Prostatectomy Compared With Radical Prostatectomy Alone in pT3 Prostate Cancer With Postoperative Undetectable Prostate-Specific Antigen: ARO 96-02/AUO AP 09/95

Abstract: Adjuvant RT for pT3 prostate cancer with postoperatively undetectable PSA significantly reduces the risk of biochemical progression. Further follow-up is needed to assess the effect on metastases-free and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
385
1
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 769 publications
(408 citation statements)
references
References 19 publications
12
385
1
10
Order By: Relevance
“…37 Indeed, we did find here that adjuvant RT was associated with a significant decrease in the risk of the outcome measure receipt of salvage therapy or progression. These data likely reflect the previouslydocumented protective effect of adjuvant RT on BCR, 4,5,36 an outcome measure which has been linked to utilization of secondary cancer treatments. 38 Moreover, additional pathological features, which may have impacted outcome, such as the presence of focal versus extensive positive margins, were not separately analyzed.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…37 Indeed, we did find here that adjuvant RT was associated with a significant decrease in the risk of the outcome measure receipt of salvage therapy or progression. These data likely reflect the previouslydocumented protective effect of adjuvant RT on BCR, 4,5,36 an outcome measure which has been linked to utilization of secondary cancer treatments. 38 Moreover, additional pathological features, which may have impacted outcome, such as the presence of focal versus extensive positive margins, were not separately analyzed.…”
Section: Discussionsupporting
confidence: 59%
“…As such, decisions to treat with adjuvant and salvage therapies were based on patient preference and physician counseling, and were thereby subject to inherent selection bias. Thus, our findings, in particular, regarding the non-significant association of adjuvant RT with disease progression and mortality must be interpreted in light of this study design, particularly as prospective randomized trials have demonstrated a benefit to adjuvant RT on reducing the risk of BCR 4,5,36 and, in one series, mortality. 37 Indeed, we did find here that adjuvant RT was associated with a significant decrease in the risk of the outcome measure receipt of salvage therapy or progression.…”
Section: Discussionmentioning
confidence: 85%
“…Three randomized multi-centre trials comparing adjuvant radiotherapy versus no adjuvant treatment for post-RP patients who had either EPE, PSM, SVI, or a combination thereof, showed fewer and/or later BCF, metastasis development and longer progression-free survival for those who received adjuvant radiotherapy. 1,2,3,23 The Southwest Oncology Group (SWOG) study by Thompson et al, 2 with longer follow-up, recently also showed an overall survival benefit with adjuvant radiotherapy compared with the 'wait and see' approach. No studies, however, have compared adjuvant therapy with early salvage therapy before PSA failure, an issue which is being addressed with another multi-center randomized controlled trial (the 'RADICALS' study).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although some studies [1][2][3][4] have found that immediate adjuvant treatment decreased the risk of biochemical failure (BCF) in patients with PSM and extracapsular tumor extension, it is not entirely clear what its effects are on distant metastasis and survival, in spite of one recent report (SWOG 8794 study) indicating a statistical advantage for early adjuvant radiotherapy. The SWOG study stated that adjuvant radiotherapy resulted in significantly reducing the risk of PSA relapse and disease recurrence compared to the 'wait and see' approach (median PSA relapse-free survival was 10.3 years for adjuvant therapy vs 3.1 years for observation and median recurrence-free was 13.8 years for adjuvant therapy vs 9.9 years for observation).…”
Section: Introductionmentioning
confidence: 99%
“…In the Wiegel trial, 1% and 0% of patients had grade 3 bladder and bowel problems. 3 This is despite patients receiving 2-dimensional RT; RT has improved greatly in target localization with image-guided techniques and my experience is that modern RT has even fewer side effects.…”
mentioning
confidence: 99%